ANALISIS PENGARUH KUALITAS PELAYANAN PERAWATAN KECANTIKANTERHADAP KEPUASAN KONSUMEN DAN LOYALITAS KONSUMEN (STUDI KASUS PADA NATASHA SKIN CARE KLINIK AMBON) - Erlinda Tehuayo (Soso-Q : Jurnal Manajemen, 2020)
Beauty clinic is a skin care service that offers products and services to protect and improve skin. Already many in the city of Ambon run a beauty clinic service business. Natasha Skin Care beauty clinic which is located in Maluku City Mall in Ambon City. Natasha Skin Care is not only for women but men can also buy products or do beauty treatments. The purposes of this study were: To determine the effect of the quality of Natasha Skin Care on customer satisfaction and customer loyalty. The samples in this study were 100 respondents who had used Natasha Skin Care Clinic services. Data collection was carried out using a questionnaire. The results of multiple analyzes and results t test proves that service quality (X1) on customer satisfaction (Y1) and customer loyalty (Y2), has a positive and significant effect.Kata Kunci: Quality and Satisfaction of Services, and Cutomer Loyalities